Adjustment Method of College Students' Mental Health Based on Data Analysis Under the Background of Positive Psychology - Yang, Sibo; Lin, Lin; Zhang, Xue (Frontiers in Psychology, 2022)
This research mainly explores the adjustment methods of college students' mental health based on virtual reality under the background of positive psychology. Importance of system requirements analysis in the software development process, analyzes the system's functional requirements, safety requirements, and software and hardware requirements, and uses the Apriori algorithm influencing factors of college students' mental health. It then designs an anomaly mining algorithm based on clustering to quickly find anomalous data health problems. The interface design of the system is concise and the operation is simple. Users can conveniently input, query, and count information according to the various controls on the interface, which fully embodies the human-oriented characteristics. Characteristics of students’ frequent Internet access to ensure the efficiency, accuracy and comprehensiveness of the evaluation and consultation work, which greatly facilitates psychological counseling teachers and students, and saves paper. Combining with positive psychology theory, it pays attention to positive experience and positive qualities of students, and builds a mental health practice system. In the experiment, the happiness index evaluation of the virtual reality treatment system group was significant, P=0.002<0.05. Its cause analysis based on actual data can provide a reliable basis for psychological educators, thereby improving the efficiency and effectiveness of school psychological counseling.